Simulation of a Quadcopter with LabVIEW - Kiss, Tamás; Szemes, Péter Tamás (International Journal of Engineering and Management Sciences, 2017)
The aim of the paper was to create a LabVIEW-based Real-Time embedded system supported development environment, which was used for the Real-Time kinematics and dynamics simulation of a quad copter as well as the adherent state-feedback controller. The state-feedback controller was designed with Linear Quadratic Regulator (LQR) based method.